Power-Aware Computer Systems 4th International Workshop, PACS 2004, Portland, OR, USA, December 5, 2004, Revised Selected Papers - Falsafi, Babak; Vijaykumar, T.N.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
Welcome to the proceedings of the Power-Aware Computer Systems (PACS 2004) workshop held in conjunction with the 37th Annual International Sym- sium on Microarchitecture (MICRO-37). The continued increase of power and energy dissipation in computer systems has resulted in higher cost, lower re- ability, and reduced battery life in portable systems. Consequently, power and energy have become ?rst-class constraints at all layers of modern computer s- tems. PACS 2004 is the fourth workshop in its series to explore techniques to reduce power and energy at all levels of computer systems and brings together academic and industry researchers. The papers in these proceedings span a wide spectrum of areas in pow- aware systems. We have grouped the papers into the following categories: (1) microarchitecture- and circuit-level techniques, (2) power-aware memory and interconnect systems, and (3) frequency- and voltage-scaling techniques. The ?rst paper in the microarchitecture group proposes banking and wri- back ?ltering to reduce register ?le power. The second paper in this group - timizes both delay and power of the issue queue by packing two instructions in each issue queue entry and by memorizing upper-order bits of the wake-up tag. The third paper proposes bit slicing the datapath to exploit narrow width operations, and the last paper proposes to migrate application threads from one core to another in a multi-core chip to address thermal problems.
Microarchitecture- and Circuit-Level Techniques -- An Optimized Front-End Physical Register File with Banking and Writeback Filtering -- Reducing Delay and Power Consumption of the Wakeup Logic Through Instruction Packing and Tag Memoization -- Bit-Sliced Datapath for Energy-Efficient High Performance Microprocessors -- Low-Overhead Core Swapping for Thermal Management -- Power-Aware Memory and Interconnect Systems -- Software-Hardware Cooperative Power Management for Main Memory -- Energy-Aware Data Prefetching for General-Purpose Programs -- Bus Power Estimation and Power-Efficient Bus Arbitration for System-on-a-Chip Embedded Systems -- Context-Independent Codes for Off-Chip Interconnects -- Frequency-/Voltage-Scaling Techniques -- Dynamic Processor Throttling for Power Efficient Computations -- Effective Dynamic Voltage Scaling Through CPU-Boundedness Detection -- Safe Overprovisioning: Using Power Limits to Increase Aggregate Throughput -- Power Consumption Breakdown on a Modern Laptop -- Erratum -- Erratum.
Keywords: Computer engineering; 9; Electronics; Computer systems; Computers; Operating systems (Computers).; Electrical engineering; Computer Engineering and Networks; Electronics and Microelectronics, Instrumentation; Computer System Implementation; Computer Hardware; Operating Systems; Electrical and Electronic Engineering